Influence of different equipment protocols on particle size determination of ground corn - Woodworth, J.C.; Nelssen, Jim L.; Goodband, Robert D.; Tokach, Michael D.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Two experiments were conducted to determine the influence of the tapping bar and sieve agitators (balls and brushes) on determining mean particle size and standard deviation of ground corn. Tapping bar had no influence (P>0.10) on mean and standard deviation; however the presence of balls and brushes on sieves decreased (P<0.002) mean particle size and increased (P<0.0001) standard deviation. These results suggest that balls and brushes should be used when determining mean particle size to assist particle flowability. More research should be conducted to determine the effects of the tapping bar and sieve agitators over a wider range of particle sizes.
Keywords: Swine; Particle size; Tapping bar; Sieve agitators